2009
DOI: 10.1111/j.1525-1446.2009.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Observed Use of Standard Precautions in Chilean Community Clinics

Abstract: Objective In Chile, little information about the use of standard precautions (SP) among health care workers (HCWs) exists. As part of a larger study to tailor and test an HIV prevention intervention for community HCWs, this study describes the observed frequency with which appropriate SP were used by HCWs in low-income community clinics of Santiago. Also, the availability of supplies is described. Sample A total of 52 structured observations with potential contamination with body fluids were done. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 10 publications
(18 reference statements)
3
16
0
5
Order By: Relevance
“…These findings are congruent with previous research documenting that stigmatization is an issue among health care workers (Cianelli, 2003; Talashek et al , 2007; Ferrer et al , 2009). Fear of contracting the disease and stereotypes related to HIV have been shown to be the primary causes of stigma towards people living with HIV.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are congruent with previous research documenting that stigmatization is an issue among health care workers (Cianelli, 2003; Talashek et al , 2007; Ferrer et al , 2009). Fear of contracting the disease and stereotypes related to HIV have been shown to be the primary causes of stigma towards people living with HIV.…”
Section: Discussionsupporting
confidence: 91%
“…Fear of contracting the disease and stereotypes related to HIV have been shown to be the primary causes of stigma towards people living with HIV. Chilean health workers fears about HIV also fostered their incorrect use of standard precautions, which is consistent with what was observed by Ferrer et al (2009) in these same Chilean community clinics. In this study, healthcare workers reported being afraid to tell their co-workers their personal serostatus due to fear of discrimination and isolation in their work place, a finding that is congruent with the study by Alvares and Ramos (2002).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Items were added to incorporate new developments such as drug treatment for reducing mother-child transmission. The questionnaire was culturally adapted for Chile based on qualitative formative evaluation (25). A modified direct translation method was used for translating the questionnaire into Spanish (26), using a team of bilingual researchers.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Such recommendations should be adopted during care provided to any patient, regardless of their diagnosis (25) . Analysis of the reasons of low or non-adherence to SP shows that many of them are related to lack or insufficient investment on work conditions, which, in addition to exposing health professionals and patients to risks, generates an atmosphere of disharmony, dissatisfaction and lack of motivation in the workplace (26) . Therefore, we stress the importance of well-established standards and routines, with well-defined and disseminated flows, so that everyone has access to them and is aware of what Chart 1 -Characterization of the articles, results of adherence to standard precautions, reasons and consequences of low adherence and recommended interventions.…”
Section: Discussionmentioning
confidence: 99%